2000
DOI: 10.1021/cc000052k
|View full text |Cite
|
Sign up to set email alerts
|

A Statistical-Based Approach To Assessing the Fidelity of Combinatorial Libraries Encoded with Electrophoric Molecular Tags. Development and Application of Tag Decode-Assisted Single Bead LC/MS Analysis

Abstract: A statistical sampling protocol is described to assess the fidelity of libraries encoded with molecular tags. The methodology, termed library QA, is based on the combined application of tag decode analysis and single bead LC/MS. The physical existence of library compounds eluted from beads is established by comparing the molecular weight predicted by tag decode with empirical measurement. The goal of sampling is to provide information on overall library fidelity and an indication of the performance of individu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 45 publications
1
30
0
Order By: Relevance
“…Carroll et al 133,134 and Dolle et al 135 utilized different techniques to produce large combinatorial statine-based libraries to identify potent Plm II inhibitors with good selectivity. In the first study a 13,020-membered library was generated based on what had been published in the literature at the time.…”
Section: Statinesmentioning
confidence: 99%
See 1 more Smart Citation
“…Carroll et al 133,134 and Dolle et al 135 utilized different techniques to produce large combinatorial statine-based libraries to identify potent Plm II inhibitors with good selectivity. In the first study a 13,020-membered library was generated based on what had been published in the literature at the time.…”
Section: Statinesmentioning
confidence: 99%
“…In contrast to the previous library, where both benzyl and isobutyl groups were tolerated in the P1 position, the benzyl was strongly favored as the P1 side chain, indicating that other parts of the inhibitor influence the overall affinity. To demonstrate a statistically based library quality assurance method a third combinatorial library containing 25,200 statines was produced and evaluated against Plm II and Cat D. 135 In this library Plm II inhibitors with significantly higher potency and selectivity were obtained (cf. inhibitors 14 and 15 with inhibitor 16, Table I).…”
Section: Statinesmentioning
confidence: 99%
“…The binomial distribution and its limiting form in the Poisson discrete probability distribution function variously describe the number of each compound type that a split-and-pool library synthesis yields, the scale required to guarantee the synthesis of all possible compounds, 13 and even the number of library members to analyze during quality control. 4 Library screening is also a numbers game; it is a process designed to generate a systematically biased subsample of the library whose members meet defined experimental criteria. As statistical processes, sampling and confidence are linked: larger sample sizes more accurately reflect the population and give the experimentalist greater confidence in hypothesis testing.…”
Section: Introductionmentioning
confidence: 99%
“…To date, the majority of the libraries encoded with chloroaromatic tags [21] have been prepared on 80^100 Wm TentaGel resin [18] which has markedly di¡erent physical properties from those of the large, hydrophobic PS support [40]. Preliminary experiments on 500^600 Wm PS macrobeads quickly revealed that previously reported encoding and decoding procedures for 801 00 Wm TentaGel were not transferable simply by scaling the procedures relative to bead size [17,41]. It was not surprising that these decoding protocols were not applicable to our hydrophobic PS support because these procedures were carried out in predominantly aqueous CAN solutions, amenable to hydrophilic TentaGel beads.…”
Section: An Optimized Binary Encoding Protocol For 500^600 Wm Ps Macrobeadsmentioning
confidence: 99%